A field and laboratory manual for sampling, processing and reporting microplastics in coastal and marine environments - Wootton, Nina; Reis-Santos, Patrick; Przeslawski, Rachel; Adyel, Tanveer M.; Blewitt, Michelle; Clarke, Bradley; Crutchett, Thomas; Ghose, Anirban; Hajbane, Sara; Hamann, Mark; Hardesty, Britta Denise; Hossain, Rumana; et al. (Frontiers in Marine Science, 2025)
Global interest in microplastics is increasing, with numerous organisations collecting data on microplastics in the environment. However, disparate sampling, analysis, and reporting methods limit our ability to integrate data, hindering a global understanding of microplastic occurrence, effects and dynamics. Drawing on international directives and collaborations, we present a comprehensive guideline of harmonised and standardised field and laboratory approaches for microplastics in marine and coastal environments. We aim to ensure data consistency and comparability, incorporating the latest methodological developments for investigating and monitoring microplastics in four environmental matrices: sediment, water, biota, and air. A participatory approach brought together 40 researchers with diverse experience, reflecting a broad range of regional and international research. We provide best practice recommendations for sample processing to isolate, quantify and characterise microplastics, along with effective quality assurance and quality control measures. We also include reporting and data release recommendations, to ensure consistency and comparability across datasets. This guideline is endorsed by Ocean Best Practices System. By following these guidelines, and incorporating workflows supporting Findable, Accessible, Interoperable, and Reusable (FAIR) data, diverse stakeholders and practitioners can generate harmonised data essential for decision-making, facilitating a collective ability to synthesise global datasets and support action on microplastics.